Two Japanese siblings affected with Chikungunya fever with different clinical courses: Imported infections from the Cook Islands. Issue 6 (27th January 2016) - Kondo, Makoto; Akachi, Shigehiro; Ando, Katsuhiko; Nomura, Tatsuma; Yamanaka, Keiichi; Mizutani, Hitoshi
Abstract: Two Japanese siblings visited the Cook Islands on business and stayed for 2 months. The sister developed a high fever, arthralgia, erythema and leg edema on the day after returning to Japan. The brother also developed neck and joint pain on the day following the sister's onset. Subsequently, his erythematous lesions spread over his whole body. Chikungunya virus was detected from the sister's blood and urine by specific reverse transcription polymerase chain reaction, but not in the brother's samples. Retrospectively, his history of Chikungunya fever was confirmed by the presence of the anti‐Chikungunya virus immunoglobulin (Ig)M and IgG antibodies using the specific enzyme‐linked immunoassay. In Japan, no autochthonous case of Chikungunya fever was reported previously. We should give attention to the imported infectious diseases for epidemic prevention. This report warns about the danger of the imported infectious diseases, and also suggests that covering the topic of infectious disease in the world is critical to doctors as well as travelers.